Dinamika Kelompok Penerima CSR PLN Tarahan Lampung Selatan - Dedeh Kurniasih Kusnani; Pudji Muljono; Amiruddin Saleh (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluh Pertanian Indonesia), 2015)
The study aims to: (1) analyze the level of group dynamics; (2) analyze relation between internal and external characteristics of members and group dynamics. The research uses survey method and was conducted in South Lampung. Numbers of samples are 50 respondents. Descriptive and correlational analysis was used to explain this research. The results of the research show that: (1) the level of group dynamics was low because the group goals are not specific, the structure is not clear, group role and function is not implemented optimally, coaching and development of group is not adequate, and there is no positive pressure; (2) the internal and external characteristics of members that related positively with group dynamics are working motivation, intensity of extension, mentoring, and social interaction of the group.Keywords: coorporate social responsibility, group dynamics, member’s characteritics, frequency of extension